Peran sosial media dalam meningkatkan kesadaran mahasiswa terhadap identitas nasional - andini, nur ania (Maliki Interdisciplinary Journal, 2025)
This research seeks to assess how social media platforms contribute to the development of students’ national identity consciousness. National identity reflects the character of a nation, encompassing shared values, culture, language, and ideals. Today, social media is no longer just a tool for communication and entertainment but has evolved into a platform for shaping public opinion and personal identity. This research employs a qualitative method with a literature review approach. This research examines various previous articles and scientific journals for analysis. The findings reveal that the intensity of social media use and the variety of content consumed significantly influence students’ awareness and understanding of national identity. Social media plays a dual role: on one hand, it can strengthen national identity, but on the other hand, it can also weaken it, depending on how it is used. Therefore, it is important to improve digital literacy and national awareness among students so that social media can be utilized positively to strengthen awareness of national identity.